The Effect of Sodium-Glucose Co-transporter 2 Inhibitors on Renal Function Among Patients with Diabetic Kidney Disease - Kaewdoungtient, Piyanut; Chirananthavat, Thanit (Journal of the Nephrology Society of Thailand, 2023)
Background: Diabetic kidney disease (DKD) is the leading cause of chronic kidney diseases worldwide. Sodium-Glucose Co-Transporter 2 Inhibitors (SGLT2i) is a new class of antidiabetic agent that has renoprotective action beyond glycemic control. However, the efficacy of SGLT2i on renal function in DKD varies in different regions of the world. There has never been any study on the effect of SGLT2i on renal function in Thai population. Methods: This is a retrospective matched-pair case control study of patients with DKD between 1 January 2015 to 31 December 2020 . Patients who were treated with SGLT2i were matched to those who were not according to age, kidney function, albuminuria and renin-angiotensin-aldosterone system inhibitors (RAASi) usage. The primary outcome was the difference in estimated glomerular filtration rate (eGFR) at 96 weeks. The secondary outcome was the change in eGFR, albuminuria and adverse effects. Results: A total of 180 matched pairs were included in the analysis. They were equivalent in age, sex, the number of RAASi usage, baseline eGFR and albuminuria. Estimated glomerular filtration rate at 96 weeks was significantly higher among SGLT2i-users compared to non-users (72.31 vs. 65.37 ml/min/1.73 m2, p = 0.031). The decline in eGFR over 96 weeks was observed in both groups but to a lesser degree among SGLT2i-users (-4.76 vs. -8.46 ml/min/1.73 m2, p = 0.001). Albuminuria at 72 and 96 weeks was also significantly lower among SGLT2i users compared to non-users. Subgroup analysis revealed the higher eGFR among SGLT2i users at 96 weeks was significant only in subgroup of patients with baseline eGFR ≥90 ml/min/1.73 m2. SGLT2i users had higher incidence of urinary tract infection. No serious adverse effects were observed in either group. Conclusion: The use of SGLT2i was associated with slower decline in eGFR and attenuation of albuminuria among patients with DKD. The use of SGLT2i was associated with increased incidence of urinary tract infection. Serious adverse events were not observed in either group.